The Dynamic of Worship and Responses of Nahdlatul Ulama Members in Bantul, Yogyakarta, Toward the Indonesian Council of Ulama's Fatwa on the Worship During the Covid-19 Pandemic - Riyanta; Imam Muhsin; Fathorrahman fathur; Saptoni (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2022)
This research explains the dynamic of worship in Bantul, Yogyakarta, as well as Nahdlatul Ulama (NU) members’ responses toward the fatwa of the Indonesian Council of Ulama (MUI) on the worship during the Covid-19 pandemic. MUI’s fatwa rose different responses ranging from obedience, resistance and ignorance. We argue that these differences stem from different characteristics of religiosity. Looking closely at this, this research studies the map of responses of NU people by focusing on the questions: (1) How was dynamic of worship during the pandemic in Bantul? (2) How did Bantul people respond to the MUI’s fatwa? (3) What factors formed the differences in their responses? The data are collected through interviews with seven informants, observation, and focused-group discussions. Through sociological analysis referring to obedience and disobedience theory, we found that the unprecedented dynamic was found in the worship during the pandemic, such as at Pleret, in the case of several Friday prayer spots in one single village. Meanwhile, the NU members’ responses to the fatwa into two patterns: reception and resistance. The forms of reception are (1) accommodation by observing all advice described in the fatwa and (2) contextualization by adjusting the advice in the fatwa to suit the local needs. It came from the structural influence of the organization of NU and people literacy. Meanwhile, the forms of resistance are (1) reactive-declarative refusal and (2) passive-permissive refusal. These patterns are influenced by a religiously fatalistic perspective and by the figures’ reluctance to prohibit people from carrying out worship normally as before the pandemic.